2012
DOI: 10.1007/s10815-012-9782-2
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis for chromosome rearrangements – one blastomere biopsy versus two blastomere biopsy

Abstract: Purpose Preimplantation Genetic Diagnosis (PGD) has proven to be a useful reproductive option for carriers of some chromosome rearrangements. The data presented in this study compares the impact of one versus two blastomere biopsy on the likelihood of achieving a PGD result, as well as the effect on subsequent embryo development and clinical outcomes. Methods IVF-PGD couples had either one or two blastomeres biopsied from all embryos with ≥7 blastomeres on day 3 post oocyte collection. These blastomeres were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The number of cells obtained was comparable to that obtained from biopsies of the trophectoderm, which allowed the collection of 2–6 cells [27], [9], [28], [29] and was far better than that obtained from biopsies of cleavage-stage embryos, which permitted the collection of only 1–2 cells [3], [11]. According to the current ESHRE PGD Consortium data collection XII, biopsies on cleavage-stage embryos have been performed in 83.3% (5085/6102) of PGD/PGS cycles in Europe, whereas only 0.1% of biopsies have been performed on blastocysts (6/6102) [5].…”
Section: Discussionmentioning
confidence: 70%
“…The number of cells obtained was comparable to that obtained from biopsies of the trophectoderm, which allowed the collection of 2–6 cells [27], [9], [28], [29] and was far better than that obtained from biopsies of cleavage-stage embryos, which permitted the collection of only 1–2 cells [3], [11]. According to the current ESHRE PGD Consortium data collection XII, biopsies on cleavage-stage embryos have been performed in 83.3% (5085/6102) of PGD/PGS cycles in Europe, whereas only 0.1% of biopsies have been performed on blastocysts (6/6102) [5].…”
Section: Discussionmentioning
confidence: 70%
“…Couples who are undergoing ICSI and PGD may be concerned about pregnancy outcome and healthy offspring. Despite the invasiveness of embryo biopsy, several previous studies demonstrated that multiple micromanipulation, polar body removal, one or two blastomere biopsy, or the combination of these do not adversely affect its further in vitro development and viability [Brodie et al 2012;Cieslak-Janzen et al 2006;Hardy et al 1990;Magli et al 2004]. In confirmation with these reports, clinical findings have demonstrated that nearly one-quarter of biopsied embryos are capable of implantation [Munne et al 2003].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, PGS aneuploidy screening is offered to patients experiencing recurrent implantation failure (RIF), which is typically defined as three or more consecutive IVF cycles without a clinical pregnancy despite the good embryo quality. For the diagnosis of genetic defects in human preimplantation embryos, embryos could theoretically be biopsied at any stage between the 2-cell and blastocyst stages [1][2][3][4][5][6][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The first study describing successful biopsy of a human embryo for PGD was performed in 3-day-old embryos, which consisted of 6-8 cleavage-stage cells [1][2][3]. Presently, biopsies of 8-cell blastomeres or blastocyst trophectoderm obtained on day 3 or 5 are performed in IVF laboratories worldwide [3][4][5][6]. Harper et al reported that biopsy of blastocyst trophectoderm on day 5 or 6 is more effective than biopsy of cleavage-stage blastomeres on day 3 [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation